2009
DOI: 10.1021/jp9037123
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Second Order Methods for the Calculation of Vertical Electronic Excitation Energies: Valence and Rydberg States in Polycyclic Aromatic Hydrocarbons

Abstract: The performance of the six second order linear response methods RPA(D), SOPPA, SOPPA(CCSD), CIS(D), CC2, and CCSD, which include either noniterative or iterative doubles contributions, has been studied in calculations of vertical excitation energies. The benchmark set consisted of 39 valence and 76 Rydberg states of benzene and five polycyclic aromatic hydrocarbons. As reference values we have used the results of the corresponding calculations with the third order method CCSDR(3), which includes noniterative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 161 publications
5
61
0
Order By: Relevance
“…57 For cyclopentanone, the band maximum and origin again coincide at 6.95 eV, however, the vertical transition energy from electron ionization is again slightly higher at 7.2 eV. 52 Comparing to the calculated energies, the CC2 values are generally too low for the Rydberg states as seen also for other systems, 60 which is somewhat overcompensated for by CCSD. It can be observed that CCSDR(3) makes a small counter-correction of around 0.1 eV to the CCSD values.…”
Section: A Excited States Of the Cycloketonesmentioning
confidence: 92%
“…57 For cyclopentanone, the band maximum and origin again coincide at 6.95 eV, however, the vertical transition energy from electron ionization is again slightly higher at 7.2 eV. 52 Comparing to the calculated energies, the CC2 values are generally too low for the Rydberg states as seen also for other systems, 60 which is somewhat overcompensated for by CCSD. It can be observed that CCSDR(3) makes a small counter-correction of around 0.1 eV to the CCSD values.…”
Section: A Excited States Of the Cycloketonesmentioning
confidence: 92%
“…[64], and a benchmark study of these methods can be found in ref. [65]. In the context of ADC(2), [66] two variants can be distinguished: the strict ADC(2)-s version, which does not include couplings between doubly excited states, and the extended ADC(2)-x version, which shows a less favorable scaling behavior with system size but includes these couplings to first order.…”
Section: Theoretical Methods For Excited Statesmentioning
confidence: 99%
“…For benzene, naphthalene, and thiophene, our self-consistent and mixed GW -BSE calculations have fairly good agreement best previous theoretical values, which are computed including contributions from singles, doubles, and triples excitations. [80][81][82] The mean absolute difference across these three molecules is 0.78 eV for G 0 W 0 -BSE, 0.68 eV for G 0 W 0 Γ LDA , 0.14 for mixed GW -BSE, 0.25 for QSGW -BSE, 0.24 for QSGW Γ LDA -BSE, and 0.25 for TDLDA. For 1,2,5-thiadiazole, the cited calculation only include singles and doubles excitations, 83 and the mean absolute difference is 1.26 eV for G 0 W 0 -BSE, 1.14 eV for G 0 W 0 Γ LDA , 0.58 eV for mixed GW -BSE, 0.33 eV for QSGW -BSE, 0.29 for GW Γ LDA -BSE, and 0.61 for TDLDA.…”
Section: ∼07 Evmentioning
confidence: 97%